Associations of Y chromosomal haplogroups with cardiometabolic risk factors and subclinical vascular measures in males during childhood and adolescence. (July 2018) - O'Keeffe, Linda M.; Howe, Laura D.; Fraser, Abigail; Hughes, Alun D.; Wade, Kaitlin H.; Anderson, Emma L.; Lawlor, Debbie A.; Erzurumluoglu, A. Mesut; Davey-Smith, George; Rodriguez, Santiago; Stergiakouli, Evie
Abstract: Background and aims: Males have greater cardiometabolic risk than females, though the reasons for this are poorly understood. The aim of this study was to examine the association between common Y chromosomal haplogroups and cardiometabolic risk during early life. Methods: In a British birth cohort, we examined the association of Y chromosomal haplogroups with trajectories of cardiometabolic risk factors from birth to 18 years and with carotid-femoral pulse wave velocity, carotid intima media thickness and left ventricular mass index at age 18. Haplogroups were grouped according to their phylogenetic relatedness into categories of R, I, E, J, G and all other haplogroups combined (T, Q, H, L, C, N and O). Risk factors included BMI, fat and lean mass, systolic blood pressure (SBP), diastolic blood pressure, pulse rate, triglycerides, high density lipoprotein cholesterol (HDL-c), non-HDL-c and c-reactive protein. Analyses were performed using multilevel models and linear regression, as appropriate. Results: Y chromosomal haplogroups were not associated with any cardiometabolic risk factors from birth to 18 years. For example, at age 18, the difference in SBP comparing each haplogroup with haplogroup R was −0.39 mmHg (95% Confidence Interval (CI): −0.75, 1.54) for haplogroup I, 2.56 mmHg (95% CI: −0.76, 5.89) for haplogroup E, −0.02 mmHg (95% CI: −2.87, 2.83) for haplogroup J, 1.28 mmHg (95% CI: −4.70, 2.13) for haplogroup G and −2.75 mmHg (95% CI: −6.38, 0.88) for all other haplogroups combined. Conclusions: Common Y chromosomal haplogroups are not associated with cardiometabolic risk factors during childhood and adolescence or with subclinical cardiovascular measures at age 18. Highlights: Common Y chromosomal haplogroups are not associated with cardiometabolic risk factors from birth to age 18. Common Y chromosomal haplogroups are not associated with cardiovascular structure and function at age 18. Common Y chromosomal haplogroups are not associated with cardiometabolic risk in males during early life.